Sustainability and environmental regional autonomous corporations in Boyacá - Colombia - Salamanca Sarmiento, Carlos Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2016)
To promote the sustained growing of economic development, this mustbe linked to social structure in order to enhance the population life qualityand environmental sustainability. In this paper are analyzed the developmentnational plans from 1990 and the guidelines which involucrate allthe regional autonomous corporations. Furthermore, the origins of environmentalsustainability problematic, related to autonomous corporationsas regional environment authorities are established. Recently, there wereattempts for articulating regional measures whit legal framework and thesectoral guidelines that govern environmental policies, whose responsibilitybelongs to autonomous corporations located in Boyacá.